Risks to Biodiversity - Jaggi, Disha; Sarathambal, C; Rathore, M; Kumar, Bhumesh (Indian Farming, 2017)
Under extreme variables (abiotic and biotic factors) natural diversity has started declining more quickly as compared to natural ways. Anthropogenic pressures have enhanced rate of extinction and biodiversity loss in many countries giving rise to serious threats; mitigating faun and flora in abundance. Principle threats tobiodiversity include habitat destruction, extinction, genetic loss,invasive alien species, diseases, climate change, pollution, population growth etc. With expanded human population, their interference with natural resources has also been increased; however the resources have started declining. Globally, total 34 recognized biodiversity hotspots needs attention in special context to restoration and conservation of natural diversity which are direct source of numerous resources required for human existence.